307 The Hospital Frailty Risk Score Independently Predicts Increased Complication Rates and Healthcare Resource Utilization After Endovascular Treatment of Ruptured Aneurysms. (1st April 2022) - Koo, Andrew B.; Elsamadicy, Aladine A.; Sarkozy, Margot; Sherman, Josiah; Reeves, Benjamin; Freedman, Isaac G.; Antonios, Joseph P.; Sujijantarat, Nanthiya; Renado, Daniela; Hebert, Ryan M.; Malhotra, Ajay; Matouk, Charles C.
Abstract : INTRODUCTION: Frailty has emerged as an important indicator of patients who are at greater risk of adverse healthcare outcomes. The Hospital Frailty Risk Score (HFRS) was recently developed utilizing ICD-10 diagnostic codes to identify frailty using routine administrative hospital data but has not been applied to the evaluation of patients with ruptured intracranial aneurysms (IAs). METHODS: A retrospective cohort study was performed using the 2016-2017 National Inpatient Sample (NIS) database. All adult patients (=18 years) undergoing endovascular treatment for IAs after subarachnoid hemorrhage were identified using ICD-10-CM diagnostic and procedural codes. Patients were categorized into three HFRS-based frailty cohorts: Low (HFRS<5), Intermediate (HFRS=5 and <15), and High (HFRS=15). Patient demographics, comorbidities, treatment modality, perioperative complications, LOS, discharge disposition, and total cost of hospital admission were assessed. A multivariate logistic regression analyses were used to identify independent predictors of prolonged LOS, increased cost and non-routine discharge. RESULTS: Of the 16, 290 patients identified, 4, 200 (25.8%) were found to be Low frailty, 9, 505 (58.3%) were Intermediate, and 2, 585 (15.9%) were High by HFRS criteria. A greater proportion of patients in the Intermediate and High frailty cohorts experienced greater than one perioperative complication than Low frailty (Low: 16.4% vs Intermediate: 61.7% vs High: 87.6%, p < 0.001). There is a step-wise increase in mean LOS (Low: 12.2 ± 9.4 days vs Intermediate: 19.0 ± 14.8 days vs High: 26.9 ± 19.3 days, p < 0.001), mean total hospital cost (Low: 62, 642 ± 39, 552 vs Intermediate:98, 415 ± 63, 042 vs High: 132, 087 ± 75, 263, p < 0.001), and non-routine discharge (Low: 20.0% vs Intermediate: 46.5% vs High: 73.9%, p < 0.001) with increasing frailty. On multivariate regression analysis, similar step-wise impact was found with increasing frailty in prolonged LOS [Intermediate: OR 1.56 (p = 0.02) and High: OR 2.82 (p < 0.001)], hospital cost [High: OR 2.01 (p = 0.001)], and non-routine discharge [Intermediate:OR 1.59 (p < 0.001) and High: OR 3.12 (p < 0.001)]. CONCLUSION: Our study is the first to use the HFRS to assess the impact of frailty on patients undergoing endovascular treatment of ruptured IAs. We found that greater frailty was associated with increased complications, prolonged LOS, higher costs, and non-routine discharge.